The transformations of organicism and the concept of motif in Schenkerian Theory - Fortes, Rafael (2021)
This article elaborates a view about Schenkerian’s Theory trajectory: from its thoughts about language and musical genealogy in the 1985’s article, Der Geist der Musikalischen Technik, until the final expression of the analytical methodology in 1935, on Der Freie Satz. It reunites the issues that motivated the development of that theory, with special focus to the concept of motif’s and the organicist metaphor’s transformations. It observes how these two aspects are developed conjunctly throughout 40 years of theoretical publications, showing the intimate connection between technical and theoretical aspects. The resolution of problems such as the musical causality and the association of ideas is investigated within those aspects, promoting philosophical and epistemological thoughts about the development of Schenker’s complex musicology. Exposing this trajectory, the article finds many key-issues that comprehend and anticipates the posterior development of what we call today as Schenkerian Analysis.